Impacts of climate and human activities on Daihai Lake in a typical semi-arid watershed, Northern China - Yajun Du; Weifeng Wan; Qingbo Li; Haifeng Zhang; Hui Qian; Jinlong Cai; Junzhi Wang; Xiaokang Zheng (PloS one, 2022)
A rapid shrinkage of Daihai Lake was found in recent decades. The present study analyzed the characteristics of Daihai Lake shrinkage and quantified the contribution of climate and human activities. The results of Mann-Kendall- Sneyers test and moving t-test showed that there was an obvious mutation point of lake level in 2006 and the descending speed of Daihai Lake level post-2006 (-0.46m/a) was 3.22 times that of pre-2006 (-0.14m/a). The centroid of Daihai Lake moved 1365.18 m from southwest to northeast during 1989 ~ 2018 with an average speed of 47.08 m/a. The results of Mann-Kendall trend test revealed that the annual evaporation showed a significant downward trend with a rate of approximately -5.33 mm/a, while no significant trend was found in precipitation. Daihai lake water level showed a very weak relationship with evaporation (r = 0.078, p < 0.01) and precipitation (p>0.05) respectively. Daihai Lake was influenced by human activities mainly from land use/ land cover, building reservoirs, pumping groundwater and directly consuming Daihai Lake water by Daihai power plant (DHPP). It was thought-provoking that DHPP began to consume Daihai lake water in 2006, which was consistent with abrupt change of Daihai lake level. The proportion of human impact was fluctuating upward. Human factors were the main factor of lake water reduction in last 10 years and the 5-year average contribution of human activities to Daihai Lake shrinkage was more than 61.99%. More attention and economic support should be given to prevent the continuous shrinkage of Daihai Lake.